SCHEDULING OF WORKING TIME OF DRIVERS IN REGULAR BUS TRANSPORT - Poliak, Milos; Forrest, Linda; Semanova, Stefania (Doprava a spoje, 2012)
In terms of regular bus transport in the Slovak Republic (SR), the work of drivers is governed by legislation such as Labour Code, Regulation (EC) No 561/2006 and Act No 462/2007 on the organization of working time in transport. Provisions of Regulation (EC) No 561/2006 are applied to operation of bus lines in excess of 50 km length. On the other hand, the operation of bus lines with a length less than 50 km is regulated by Act No 462/2007.